Analisis Sukuk Negara Sebagai Alternatif Pembiayaan APBN - Rahmawati, Miftahul (An-Nisbah: Jurnal Ekonomi Syariah, 2018)
Abstrak This study used a descriptive qualitative approach that analyzed the potential of the State sukuk and the mechanism of sukuk issuance to finance the project. To answer the first problem, we use the method of forcasting or time series using ARCH-GARCH model with the help of eviews7, ARCH-GARCH is an econometric model introduced by Engle (1982) and developed Bollerslev (1986). In its development the ARCH-GARCH model became the mainstay for time series analysis on the capital market, which shows the volatility estimator. In this research, we have found the standard error 7813.429 and forcast resulted in the range of 10,000 to 20,000 in 2018. and answer the second problem, this research uses qualitative and has information from interview to sharia financing directorate, finance ministry. The result is that the State Sukuk has the potential to finance the project. Abstrak Penelitian ini menggunakan pendekatan kualitatif deskriptif yang menganalisis potensi sukuk Negara dan mekanisme penerbitan sukuk untuk membiayai proyek. Untuk menjawab berapa masalah yang pertama, digunakan metode forcasting atau time series menggunakan model ARCH-GARCH dengan bantuan eviews7,ARCH-GARCH adalah model ekonometrik yang diperkenalkan oleh Engle (1982) dan dikembangkan Bollerslev (1986). Pada perkembangannya model ARCH-GARCH menjadi andalan untuk analisis time series pada pasar modal, yang menunjukkan penduga volatilitas. Dalam penelitian ini, telah ditemukan standard error 7813.429 dan forcast menghasilkan kisaran 10.000 sampai 20.000 pada tahun 2018. dan menjawab masalah yang kedua, penelitian ini menggunakan kualitatif dan dilengkapi informasi dari hasil wawancara kepada direktorat pembiayaan syariah, kementrian keuangan. Hasilnya adalah Sukuk Negara sangat berpotensi untuk membiayai proyek.